Bioinformatics-Inspired Algorithms for 2D-Image Analysis—Application to Medical Images Part II: Images in Circular Format - Neelakanta, Perambur S; Pappusetty, Deepti; Bertot, Edward M (International journal of biomedical and clinical engineering, 2012)
This paper describes a new method of comparing images of circular/near-circular symmetry so as to elucidate the similarity details between them. If one such image is a test-entity and the other is a reference template, the comparison in question will lead to find the unique features (and their locations) in the test-image vis-à-vis the template. The method of comparison and similarity assessment indicated thereof is to use the so-called Needleman-Wunsch (NW) and Smith-Waterman (SW) algorithms commonly adopted in bioinformatic contexts of comparing two linear sequences (like DNA chains). Relevant procedure is extended in this study to address 2D-patterns. It involves first transforming the test-image (of circular symmetry) from polar-plane to a rectangular format. Next, the transformed test-image is digitised and compared against a template (also in digital rectangular format) on row-to-row and column-to-column basis. The resulting alignment of pixel bits in the test-image versus the template leads to an optimal score-of-similarity on the comparisons made. Biomedical applications of the proposed strategy are explored with reference to typical and circular/quasi-circular MRI images, and the associated image recognition, interpretation, and locating of the artefacts are discussed.